(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
In the field of civil engineering, cement concrete is a building material that is utilised extensively across the board. However, there are certain worries about its tensile strength. Many academics have conducted study to find a remedy. Fibre strengthening is the most effective and flexible technique to increase after crack tensile strength and energy absorption capacity. Plain concrete was manufactured with Portland cement, fine and coarse aggregate, flyash, silicafume, and waterreducing admixtures. Without modifying the concrete components, steel fibre reinforced concrete specimens with aspect ratios of 70 and 50 and volume fractions of 0.25, 0.5%, and 0.75 were constructed. Using 12mm synthetic polyester fibres, we made 0.75, 1%, and 2% polyester fibre reinforced concrete. Steel and polyester fibres were mixed in volume ratios of 0.5:0.6, 0.5:0.7, 0.5:1.0, 0.5:2.0, 0.75:1.5, and 0.75:2.0 to create composite fibre reinforced concrete samples. We used IS 516-1956 and IS 5816-1999 to test fibre-reinforced and composite-reinforced concrete. All fibre-reinforced single and hybrid specimens improved tensile and flexural strength over plain concrete. Steel-polyester composite fibres outperform single-fibre reinforced concrete because of their synergistic impact. Schrader drop weight impact testing was used to determine disc fracture and failure. Each 160 mm cylinder specimen was examined using the Brazilian method to measure its energy-intake capacity under split tensile loading. The 120-220 mm cylinder specimens were all compressed uniaxially. Area under load deformation curves was drawn for each loading conditions and those areas were used to determine the energy In-take capacity Adding polyester, steel, or hybrid fibre to concrete boosts its compressive strength. The polyester/steel combination increases split tensile strength.